Detection of carnosinase-1 in urine of healthy individuals and patients with type 2 diabetes: correlation with albuminuria and renal function - Rodriguez-Niño, Angelica; Braun, Jana D.; Zhang, Shiqi; Albrecht, Thomas; Qiu, Jiedong; Krämer, Bernhard; Herold, Anna; Hauske, Sibylle J.; Yard, Benito A. (Amino acids, 2019)
Low serum carnosinase (CN-1) concentrations are associated with low risk for development of diabetic nephropathy (DN) in patients with type 2 diabetes (T2D). Although CN-1 is expressed in the kidney, urinary CN-1 (CNU) excretion and its pathological relevance in patients with T2D have not been investigated to date. The present study therefore assessed the extent of CNU excretion in healthy subjects (n = 243) and in patients with T2D (n = 361) enrolled in the DIAbetes and LifEstyle Cohort Twente-1 (DIALECT-1) in relation to functional renal parameters. CNU was detected in a high proportion of healthy individuals, 180 (74%); median CNU excretion was 0.25 mg/24 h [(IQR 0-0.65 mg/24 h]. In patients with T2D the prevalence and extent of CNU increased in parallel with albuminuria (r = 0.59, p < 0.0001; median CNU 0.1 vs 0.2 vs 1.5 mg/24 h, p < 0.0001; prevalence of CNU 61 vs. 81 vs. 97% p < 0.05 in normo- (n = 241), micro- (n = 80) and macroalbuminuria (n = 40), respectively). Patients with estimated glomerular filtration rate (eGFR) < 30 ml/min/1.73 m2 displayed higher median CNU excretion rates in comparison to patients with preserved eGFR (> 90 ml/min/1.73 m2) (1.36 vs 0.13 mg/24 h, p < 0.05). Backward stepwise multivariate linear regression analysis revealed albuminuria, eGFR and glycosuria to be independent factors of CNU excretion rates, all together explaining 37% of variation of CNU excretion rates (R2 = 0.37, p < 0.0001). These results show for the first time that CN-1 can be detected in urine and warrants prospective studies to assess the relevance of CNU for renal function deterioration in diabetes patients.